Corporate success stories in the UAE : the key drivers behind their growth - Vel, Prakash; Gomiscek, Bostjan (Emerald Publishing Limited, 2021)
In the domains of business and management, organizations across the world imbue insiders and outsiders with multiple 'strategies of success' that can be learnt from them. 'Corporate Success Stories In The UAE' is a rich collection of these evidence-based cases that have led to the success of various companies in the United Arab Emirates. The corporate milieu has been transforming at a rapid pace in the last decade and companies are constantly in an endeavour to craft suitable strategies to survive and progress during normal and critical business environments, including the recent COVID -19 scenario. This accentuates the need for having regionally contextualised knowledge inputs needed to enhance strategic thinking among the corporate decision makers and the academic fraternity. Regional 'Case studies' have been a major tool for such knowledge enhancement. This book is a focused attempt at bringing out case studies on 13 successful companies in the UAE, belonging to different sectors and industries. All cases come with 'Teaching notes' and 'Summary presentations' to cater to the needs of corporate managers to train their employees, lecturers to train their undergraduate and post graduate students. The cases have been prepared to serve three major target audiences namely Company managers, Universities professors and Researchers. The chapters in the book provide rich insight on the companies, their products and services, key indicators of success and the strategic drivers behind them and finally the potential areas of future study. Thus, the book serves as a repository of curated best practices across industries in the UAE.
Includes index.
Keywords: Business planning -- United Arab Emirates -- Case studies.; Strategic planning -- United Arab Emirates -- Case studies.; Success in business -- United Arab Emirates -- Case studies.; Business & Economics -- Strategic Planning.; Business strategy.; elektronické knihy; electronic books